Pengaruh Variasi Fraksi Volume Pada Biokomposit Serat Kulit Buah Pinang/ Serat Pelepah Pisang/ Matriks LDPE Terhadap Kekuatan Bending Dan Penyerapan Air - Jayantara, Kadek; Kencanawati, Cok Istri Putri Kusuma; Priambadi, I Gusti Ngurah (Teknik Desain Mekanika; Vol 11 No 2 (2022): April 2022 : Teknik Desain Mekanika, 2022)
Abstract The development of the manufacturing industry in the material sector in the era of globalization is always required to be more enviromentally friendly. The development of composite materials is expected to replace synthetic fiber composites to natural fiber composites. The use of biomaterials is one solution in overcoming environmental problems. One biomaterial that can be utilized in composites is betel nut skin fiber and banana leaf fiber. The test was carried out by combining banana leaf fiber and betel nut skin fiber combined with LDPE type plastic and varying the fiber volume fraction at 2,5%, 5%, 7,5%, 10%, 12,5% and treatment was carried out on fiber in solution with a percentage of 5% NaOH. The composite manufacturing process use ASTM D790-03 reference for bending test and ASTM D570-98 for water absorption. Micro photo observation using Nikon Eclipse LV150 microscope with 5X magnification. The higher the percentage of volume fractions there is a decrease in strength in the composite. The highest bending strength is found in the 5% fiber volume fraction with an average bending strength value of 11,478 Mpa. In water absorption the highest value is found in the fraction of fiber volume of 10% with a value of 11,03%. The bond between the fiber and the matrix can be seen from morphological observations through micro photo. Keywords: Banana leaf fiber, betel nut skin fiber, hybrid composite